Evaluation of the mechanical cleaning efficacy of dental handpieces. Issue 1 (September 2019) - Offner, Damien; Brisset, Lucien; Musset, Anne-Marie
Summary: Background: Dental handpieces undergo a decontamination process before reutilization. Thorough cleaning is a prerequisite to effective sterilization, to guarantee safety and prevent cross-infections. Aim: To assess the cleaning efficacy offered by devices dedicated to dental handpieces. Methods: PIDTests©, which are patented tubes made of transparent material and designed to replace handpieces in cleaning devices, were artificially stained by Soil Test© (Browne/STERIS). Three cycles were performed with PIDTests© connected to every handpiece adapter in the four different machines tested: X-Cid 2© (Micro-Mega) with a total of nine PIDTests©; iCare+© (NSK) with nine PIDTests©; DAC Universal© (W&H) with 18 PIDTests©; and BioDA 80© (VR2M) with 24 PIDTests©. A visual evaluation and a biuret reaction test were performed. Findings: In three of the tested cleaning devices (X-Cid2©, iCare+© and DAC Universal©), all of the PIDTests© showed Soil Test© residues, on the internal and external surfaces indicating cleaning was ineffective. Only the BioDA 80© showed no residual stains on all the PIDTests© and negative biuret reaction test results, making the cleaning effective. Conclusions: Manufacturers should optimize the cleaning device parameters, based on the Sinner circle (grouping compensatory parameters which influence the effectiveness of a cleaning process, such as pressure, temperature, time, detergent concentration), to improve cleaning efficacy and enable dental surgeons to ensure the safety. Although PIDTests© are the only tool to provide visual indications on the cleaning efficacy of washer-disinfectors dedicated to handpieces, manufacturers should continue with the development of improved and validated tools to assess cleaning efficacy.